Reporting a Transcript from Iranian Viola Tricolor, Which May Encode a Novel Cyclotide-Like Precursor: Molecular and in silico Studies. (February 2020) - Khoshkam, Zahra; Zarrabi, Mahboobeh; Sepehrizadeh, Zargham; Naghdi, Elmira; Aftabi, Younes
Graphical abstract: Viola tricolor (Pansy) is a well-known herb in the traditional medicine prescribes and its bioactive peptides have been introduced as responsible for these remediation characteristics. Cyclotides are one of the most important groups of these peptides. They have a circular structure consisting of 28-37 amino acids and could be useful in biotechnology and drug design. Here, we described a potentially novel cyclotide-like precursor (GenBank accession number: KP065812) from V. tricolor and its homolog sequences from many other plants. Surprisingly, they all exhibit some different features from previously introduced cyclotide precursors. These results may open up a new line in the research on the distribution and evolution of cyclotide genes in plants. Highlights: A potentially novel gene product suggested here, which may encode a cyclotide-like precursor with a conserved ER-signal sequence, a cysteine-rich sequence forming 2 zin. finger motifs and a cyclotide-like region containing two highly conserved C residues. in silico studies have provided interesting homologies between the suggested cyclotide-like precursor and several other unidentified sequences. Three-dimensional prediction of cyclotide-like precursor demonstrates unusual structure without CCK motif. This report may challenge the current viewpoints about the evolution of cyclotides. Abstract: The cyclotides are the largest known family of cyclic proteins, which are found in several plant families including Violaceae. They are circular bioactive peptides consisting of 28-37 amino acids, which possess a cyclic cystine knot (CCK) motif and could be useful in biotechnology and drug design as scaffolds for peptide-based drugs. This study describes our finding of a potentially novel gene transcript from the petals of the Iranian Viola tricolor ( V. tricolor ) flowers. This study is based on the cDNA screening method employed for isolation of cyclotide precursor genes and in silico analysis. Our study resulted in the finding of a novel cyclotide-like precursor from V. tricolor, which is documented in the NCBI by GenBank accession number: KP065812. The in silico analysis revealed that there are lots of similar sequences in many other plant families and they all exhibit some different features from previously discovered cyclotide precursors. The differences occur particularly in the main cyclotide domain that exists without the usual CCK structure. All of these hypothetical precursors have a conserved ER-signal sequence, a Cysteine (C)-rich sequence forming two zinc finger motifs and a cyclotide-like region containing several conserved elements including two highly conserved C residues. In conclusion, using the cDNA screening method we found a potentially new cyclotide-like precursor gene and in silico studies revealed its significant characteristics that may open up a new research line on the distribution and evolution of cyclotides.